Mapping dialogical action between teachers and students of the Lumad Bakwit school - Regaspi, Stefanie Marie S. (College of Arts and Letters, University of the Philippines Diliman, 2019)
In the face of rampant militarization and the oppressive structures that they are confronted with, Lumad communities have remained resilient in exemplifying their unwavering courage to move forward. A manifestation of such courage is their establishment of the Lumad Bakwit School, a makeshift school that operates amidst the community's pagbabakwit or evacuation from their home communities occupied by military personnel and paramilitary groups. The Lumad Bakwit School is comprised of teachers and students. The teachers are either teachers originally from the Lumad schools back in the community's homeland, who also participate in the pagbabakwit, or volunteer teachers who share the same advocacies of the school, which is to provide national, scientific, and mass-oriented education to the Lumad. On the other hand, the students of the school are native Lumad youth and elders, however it is the youth (aged 10-20 years old on average) that mostly makes up the school's student population. Because of the unique set-up of the school and the available conditions for them to meet every single day, transactional interactions between the teachers and students are inevitable. Dialogue, in this sense, constitutes a bulk of their interactions, thus establishing the co-authored process of meaning-making in their education. This study focused on the determination of dialogical action in the pedagogical setting of the Lumad Bakwit School. The specific research objectives were 1)to describe the Lumad Bakwit School teacher-student transactions in the pedagogical settings as reflected in the interviews with the school's teachers and students and in the in-class observation, 2)to determine the existence of dialogical action between teachers and students in the pedagogical setting within the Lumad Bakwit School by identifying and analyzing the elements of dialogical action in their transactions, and 3)to describe the role of dialogical action the pedagogical setting of the Lumad Bakwit School. The study used Paulo Freire's (1970) Theory of Dialogical Action as its theoretical framework, while the transactional model of instructional communication by McCroskey, Mottet, and Richmond (2006) was used to categorize the interactions that the researcher analyzed. The participants of the were three (3) Lumad Bakwit School teachers and three (3) Lumad Bakwit School students. Purposive sampling was used to select the participants. These participants were interviewed in the current locations of the Lumad Bakwit School at the time of the study, which were in the College of Home Economics (CHE), Gusali 2 and College of Social Work and Community Development (CSWCD), establishments of the University of the Philippines - Diliman, Quezon city. In addition, the researcher performed one (1) participant-observation session in one of their classes, which was made up of 24 students, 5 volunteer teachers, and one (1) regular Lumad Bakwit School teacher. The findings of the study showed that dialogical action exists within the pedagogical setting of the Lumad Bakwit School. The elements of dialogical action, namely cooperation, unity for liberation, organization, and cultural synthesis, and their overlaps with each other were found to exist within the pedagogical transactional interactionsof the teachers and the students. Supporting this analysis are the supplementary findings from the in-class participant-observation session, wherein transactions between the teachers and students were essential in the discussion. Also, the findings and analysis of the study showed that the teachers and students' shared consciousness of their oppressive state is echoed outside the classroom and incorporated into their struggle to be liberated from these oppressive structures. Dialogical action the pedagogical setting of the Lumad Bakwit School therefore plays a vital role in the Lumad Bakwit School's assertion of their rights and pursuit of their goals.